The Effect of Levers of Control and Leadership Style on Creativity - Maria Paramastri Hayuning Adi; Aegisia Sukmawati (Faculty of Economics and Business, Universitas Gadjah Mada, 2020)
Introduction: This research aims to investigate how leadership assists the levers of control (LOC) to influence employees’ creativity. Background problem: Managing a company is challenging due to the numerous issues faced, including those relating to the employees’ creativity. Prior studies showed different results concerning how company controls constrained or enhanced the employees’ creativity. Previous studies explained that incentives can influence the employees’ creativity, but only temporarily. However, organizations require creativity continuously in order to sustain themselves. In response to this issue, it is essential to investigate other determinants that encourage employees’ creativity, and how the process is relevant to each organization’s core values. This study examines this through companies control systems and leadership aspects. Novelty: Our study attempts to complement previous studies and answer Spekle’s (2017) call. This study offers transformational leadership to strengthen employees’ creativity, aligned through the LOC. Research Methods: The data were collected via an online survey. The questionnaires were sent to startup companies’ employees who had worked in the creative divisions of those companies for a minimum of six months. There were 109 responses that we processed. This study used SEM-PLS to analyze the data. Finding/ Result: The LOC positively influenced employee creativity. The more leaders behaved as transformational leader, it strengthened LOC to influence employees’ creativity. Conclusion: This study shows that the dimensions used to establish the LOC should be integrated, to align the employees’ creative ideas for new methods of working. Furthermore, this study supports the prior research into the self-determination theory and answers Spekle et al (2017), that leadership is required to influence the employees. Particularly, companies should appoint appropriate leaders to encourage their employees’ creativity. Transformational leaders should be considered to be an option.